Prospect of targeting lysine methyltransferase NSD3 for tumor therapy - Dan Li; Tiantian Tian; Chung-Nga Ko; Chao Yang (Elsevier, 2023)
Nuclear receptor binding SET domain protein 3 (NSD3) has recently been recognized as a new epigenetic target in the fight against cancer. NSD3, which is amplified, overexpressed or mutated in a variety of tumors, promotes tumor development by regulating the cell cycle, apoptosis, DNA repair and EMT. Therefore, the inhibition, silencing or knockdown of NSD3 are highly promising antitumor strategies. This paper summarizes the structure and biological functions of NSD3 with an emphasis on its carcinogenic or cancer-promoting activity. The development of NSD3-specific inhibitors or degraders is also discussed and reviewed in this paper.